K-Means Cluster with Calinski Harabasz Index Evaluation to Map Forest Degradation and Deforestation Areas - Ummi Rahimah; Shantika Martha; Nurfitri Imro'ah (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2026)
Although Indonesia is home to a rich biodiversity, the country is threatenedby forest degradation and deforestation, particularly in West Kalimantan. As asignificant contributor to the agricultural sector’s gross domestic product (PDRB), the Sanggau Regency is vital for preserving the environment and promoting sustainable development. This research uses the K-Means Cluster to categorize regions in Sanggau that can potentially experience forest degradation. Then, the Calinski Harabasz Index will be used to determine which clusters are the most effective. Two thousand twentythree, the research findings revealed five ideal clusters, each with a Calinski Harabasz Index value of 3.87. The first cluster consists of one sub-district, the second cluster consists of three sub-districts, the third cluster consists of two sub-districts, the fourth cluster consists of five sub-districts, and the fifth cluster consists of four sub-districts, which are all included in the distribution of clusters. A map illustrating the degree of urgency associated with forest degradation is produced as a result of this study. The map serves as a strategic reference for the government of Sanggau in its efforts to reduce theforest’s degradation and develop areas per the peculiarities of each sub-districts.